1983
DOI: 10.1111/j.1365-2141.1983.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Esterase cytochemistry in primary myelodysplastic syndromes and megaloblastic anaemias: demonstration of abnormal staining patterns associated with dysmyelopoiesis

Abstract: Summary. Acid alpha naphthyl acetate esterase (ANAE) and combined ANAE‐chloroacetate esterase cytochemistry was performed on 121 bone marrow aspirates from primary myelodysplastic syndromes (MDS) and a secondary dysplasia—megaloblastic anaemia (MA). The investigation demonstrated the presence of abnormal ANAE positive granulocyte populations in a significant proportion of cases. These cells, in which the staining patterns were characterized by atypical granular ANAE positivity and double ANAE‐chloroacetate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In contrast to the findings of Tavassoli et a1 (17), blasts were not seen to simultaneously express significant ANAE and CAE enzyme activities. These 'double-esterase' positive cells were, however, occasionally seen in more mature coexisting granulocyte populations, the existence of which we consider to reflect secondary dys-myelopoiesis (18)(19) and to be independent of leukaernic category.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In contrast to the findings of Tavassoli et a1 (17), blasts were not seen to simultaneously express significant ANAE and CAE enzyme activities. These 'double-esterase' positive cells were, however, occasionally seen in more mature coexisting granulocyte populations, the existence of which we consider to reflect secondary dys-myelopoiesis (18)(19) and to be independent of leukaernic category.…”
Section: Discussionmentioning
confidence: 78%
“…The proportions of blasts expressing thevarious mo- nocyte-associated membrane determinants was, in 26/35 cases, reasonably consistent. In these, Mcabdefined monocytic components were found to comprise 10-30% blasts in 18 cases, 30-60% in 6 and 60% positive in 2. As with ANAE cytochemistry, however, the remaining 9 cases showed considerable phenotypic heterogeneity.…”
Section: Monoclonal Antibody Studies (Table 3)mentioning
confidence: 90%
“…The co-inheritance of α-thalassemia with transfusion-dependent β-thalassemia is an important factor in producing milder forms of thalassemia major [18]. Studies showed that patients who co-inherited the 2 α-globin gene deletion showed less severe clinical outcomes [19].…”
Section: Discussionmentioning
confidence: 99%